Multidisciplinary design of a high lift device using shape memory alloy actuator - Amir, Shakirin; Abdullah, Ermira Junita (The Aeronautical and Astronautical Society of the Republic of China, 2024)
Design of morphing wing poses a multi-disciplinary challenge involving aerodynamics, structure, material, control and system integration. The design process requires iterations and trade-offs to achieve the optimal solution that meets the design objective. In this study, design methodology for a morphing wing as a high lift device using the shape memory alloy actuator (SMA) is presented. The use of SMA in the design offers greater advantage compared to conventional actuator but it also further increases the design complexity. For this research work, a novel high lift device is designed to fulfill the design requirements of a wing with flexible trailing edge deflection. Computational fluid dynamics analysis (CFD) is used to assess the changes of aerodynamics forces. Finite element analysis (FEA) is used to predict the structural changes required. The SMA actuator is designed to provide the required actuation force to achieve the trailing edge deflection. A wind tunnel testing is performed to verify the lift and drag coefficient produced by the high lift device. On the whole, it has been found that the novel design of high lift device is capable of improvement in lift coefficient and the experimental test has also demonstrated an increase of lift-to-drag (L/D) ratio at lower angle of attack of 4° where the L/D for the original wing was 3.806 and the L/D for the wing with trailing edge down was 8.